Implementing School-Based Management to Improve Educational Quality - Isnaini subaro; Widya Andriyani; M. Syukron Maksum; Salis Masruhi (Al-Qalam Institue, 2025)
This study aims to analyze the concept, objectives, legal foundations, characteristics, and implementation of School-Based Management (SBM) as a strategy for improving educational quality in the era of decentralization. The research employed a qualitative approach using a library research design. Data were collected from books, peer-reviewed journal articles, policy documents, and relevant educational regulations, and analyzed through descriptive-analytical content analysis. The findings indicate that the successful implementation of SBM is strongly influenced by a paradigm shift in school management, democratic leadership of school principals, active involvement of school committees and the community, and systematic school planning through the School Development Plan. SBM is not merely an administrative policy but a comprehensive managerial approach that promotes school autonomy and supports continuous improvement in educational quality. The implications of this study suggest that consistent and context-sensitive implementation of SBM is essential for strengthening effective school governance and achieving sustainable educational quality improvement, particularly within decentralized education systems